Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1002/anie.201610491
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism‐Based Fluorogenic trans‐Cyclooctene–Tetrazine Cycloaddition

Abstract: The development of fluorogenic reactions which lead to the formation of fluorescent products from two nonfluorescent starting materials is highly desirable, but challenging. Reported herein is a new concept of fluorescent product formation upon the inverse electron‐demand Diels–Alder reaction of 1,2,4,5‐tetrazines with particular trans‐cyclooctene (TCO) isomers. In sharp contrast to known fluorogenic reagents the presented chemistry leads to the rapid formation of unprecedented fluorescent 1,4‐dihydropyridazin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
60
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 68 publications
(65 citation statements)
references
References 51 publications
2
60
0
1
Order By: Relevance
“…[8] As eries of experimentsa nd calculations confirmed the identityo f1,4-dihydropyridazines as the actual fluorescent speciesf ormed during the reaction( see the Supporting Information).W ed etermined the photophysical properties of the correspondingc lick products,w hich are summarized in Ta ble 1. [8] As eries of experimentsa nd calculations confirmed the identityo f1,4-dihydropyridazines as the actual fluorescent speciesf ormed during the reaction( see the Supporting Information).W ed etermined the photophysical properties of the correspondingc lick products,w hich are summarized in Ta ble 1.…”
Section: Synthesis Of Aza-tcosmentioning
confidence: 72%
See 2 more Smart Citations
“…[8] As eries of experimentsa nd calculations confirmed the identityo f1,4-dihydropyridazines as the actual fluorescent speciesf ormed during the reaction( see the Supporting Information).W ed etermined the photophysical properties of the correspondingc lick products,w hich are summarized in Ta ble 1. [8] As eries of experimentsa nd calculations confirmed the identityo f1,4-dihydropyridazines as the actual fluorescent speciesf ormed during the reaction( see the Supporting Information).W ed etermined the photophysical properties of the correspondingc lick products,w hich are summarized in Ta ble 1.…”
Section: Synthesis Of Aza-tcosmentioning
confidence: 72%
“…Am uch less common situation represents fluorogenic ligations in which the formation of the fluorophore is an inherentr esult of the chemicalr eaction. [8] Althoughw ecould demonstrate the powero ft his chemistry for bioimaging, we also found that by modifying the hydroxyl groupo ft he ax-TCO-ol, the fluorogenic properties of the reaction alter or even completely disappear.F or many reasons,i t wouldb ea dvantageous to maintain the fluorogenic nature of the reactionw hilee nabling attachmento fv ariousu seful functionalg roups to, for example, biomolecules. [6] Shang et al recently reported ac onceptually similars tyrene-tetrazinec ycloaddition leadingt of luorescent dihydropyridazines.…”
Section: Introductionmentioning
confidence: 79%
See 1 more Smart Citation
“…[4] Ag ood match between the LUMO tetrazine and HOMO dienophile endows tetrazine-based iEDDAr eactions with fast bimolecular kinetics compared to other click reactions.T he rate constants are as high as 10 6 m À1 s À1 under physiological conditions. [6,7] Recently,a nother class of bioorthogonal click reactions,namely between sydnones and strained alkynes,h as been developed. Forc yclooctene dienophiles,slow tautomerisation ensues in protic solvents to yield the 1,4-dihydro isomer.…”
mentioning
confidence: 99%
“…60 fs). [6,7] b) Cycloaddition between asydnone and astrained alkyne. [16] An internal residue within the transmembrane b barrel of the aHL pore is modified with ar eactant of interest.…”
mentioning
confidence: 99%